Hot Rod Hamster and the awesome ATV adventure! - Lord, Cynthia; Anderson, Derek, 1969-; Paprocki, Greg (New York : Scholastic Inc., 2015)
During their trail ride on all-terrain vehicles, Hot Rod Hamster and his friends stop to help Grandpa Dog and two puppies, whose vehicle has tipped over and gotten stuck in the mud.
300
Keywords: All terrain vehicles -- Fiction; Hamsters -- Fiction; Dogs -- Fiction; Mice -- Fiction